PEMBERDAYAAN GURU-GURU SMA/SMK UNTUK MENINGKATKAN PEMAHAMAN TENTANG GAME TECH MELALUI WORKSHOP PEMBUATAN GAME ANIMASI BERBASIS 3D DI PRONOJIWO KAB. LUMAJANG - Alexius Endy Budianto; Yusriel Ardian (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Community service is one part that cannot separate from the Tri Dharma of Higher Education. In this service, we from the Faculty of Science & Technology of Kanjuruhan University will train high school / vocational teachers in Pronojiwo Lumajang Regency and Workshop participants to understand the Importance of the Role of Game Tech in the global era. Workshop participants in this service are high school / vocational school teachers and the general public in the Pronojiwo area, Lumajang Regency. Most of the participants still did not optimize the function and role of the game, especially Game Tech. Besides, they also the public and the public still use technology as a medium of information and communication, so it is very appropriate to be given an understanding of game technology through a workshop on making this 3D-based animation game by optimizing the technology available to participants. The method used in community service is a workshop on making 3D-based animation games in Pronojiwo District. Lumajang to maximize the understanding of technology that exists in the teachers and participants in particular so that participants can understand and can use these technologies to support the scientific and technological insights of the game from each participant.